The foundation of social finance: what can Islamic finance and Islamic social finance learn? - Azrai Azaimi Ambrose, Azniza Hartini (2019)
Even though Islamic Finance offers a set of distinct concepts, it is often blamed for replicating the conventional finance practices. The same could happen to Islamic Social Finance. Although Islamic Social Finance is an emerging field of study like social finance, the literature of the latter has more deliberations on its foundational concept than the former. As such, this paper attempts to address this conundrum by taking lessons from the literature developments of social finance. Specifically, this paper aims to (1) trace the roots of social finance and (2) compare and contrast the key concepts of social finance, Islamic Finance, and Islamic Social Finance. Findings shows that Islamic Finance and Islamic Social Finance should mediate the theories of conventional finance, concepts in social finance, the practice of both fields, and the Shari’ah in order to rediscover their identities and theoretical underpinnings.